Na2GaS2Cl: a new sodium-rich chalcohalide with two-dimensional [GaS2]∞ layers and wide interlayer space. Issue 32 (30th July 2021) - Li, Xiaoshuang; Liang, Fei; Liu, Tianpeng; Li, Haifeng
Abstract : A new sodium-rich chalcohalide Na2 GaS2 Cl has a 2D layered structure constructed from supertetrahedra and wide interlayer distances around 4 Å. Abstract : By introducing halogens to the A/Ga/Q (A = Na, K; Q = S, Se) system, one new chalcohalide namely Na2 GaS2 Cl was successfully obtained. It crystallizes in the orthorhombic space group Cmcm (63). Na2 GaS2 Cl has a layered structure consisting of two dimensional [GaS2 ]∞ layers which are stacked in "face to face" and "back to back" arrays and separated by Na + and Cl − ions. Interestingly, supertetrahedral building units [Ga4 S10 ] (T2) which are rarely found in metal chalcogenides and metal chalcohalides are formed in this structure. Moreover, the distances of two adjacent layers are around four times larger than the ionic radius of the Na + ion, which is very likely to provide a perfect environment for the storage and migration of Na + ions. In particular, the volume concentration of the Na + cations in this compound is as high as 1.54 × 10 22 cm −3 . The UV-vis-NIR spectroscopy measurement reveals that the optical band gap of this title compound is 3.06 eV. The electronic structural calculations on Na2 GaS2 Cl show that the band gap is mainly determined by the [GaS4 ] groups and Na–Cl ionic bonding.